A Scale for Describing Levels of Confirmation/Replication in Evaluation - Michael Scriven (The Evaluation Center at Western Michigan University, 2006)
In order to support both the validity and credibility of claims about program or product merit or worth, we often turn to evaluation. There are various ways in which evaluation can be conducted or managed, which themselves have differing levels of validity and credibility. The following scale can be used descriptively to indicate these levels, following the usual view of scientific method which identifies confirmation by others as a major criterion of validity. The higher numbers are not necessarily more valid, though they are generally more credible. Keep your sense of humor when reading this; it's not only meant to be serious!